2008
DOI: 10.3727/096368908784423256
|View full text |Cite
|
Sign up to set email alerts
|

Intraputamenal Infusion of Exogenous Neurturin Protein Restores Motor and Dopaminergic Function in the Globus Pallidus of MPTP-Lesioned Rhesus Monkeys

Abstract: The neurorestorative effects of exogenous neurturin (NTN) delivered directly into the putamen via multiport catheters were studied in 10 MPTP-lesioned rhesus monkeys expressing stable parkinsonism. The parkinsonian animals were blindly assigned to receive coded solutions containing either vehicle (n = 5) or NTN (n = 5, 30 µg/day). Both solutions were coinfused with heparin using convection-enhanced delivery for 3 months. The NTN recipients showed a significant and sustained behavioral improvement in their park… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 32 publications
2
34
0
2
Order By: Relevance
“…Intrastriatal injections of NTN in rodent models of PD have demonstrated neuroprotective and neuroregenerative effects on dopaminergic nigrostiatal function, 28,29 and most recently, intraputamenal infusion in the globus pallidus of MPTP-lesioned rhesus monkeys showed behavioral improvement and elevated locomotor activity levels. 30 Nevertheless, in this study, it was shown that FUS in conjunction with microbubbles can induce high levels of NTN bioavailability through the safely opened BBB volume, and increased bioactivity, indicating the strong therapeutic potential for Parkinson's and other neurodegenerative diseases of this noninvasive drug delivery methodology.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Intrastriatal injections of NTN in rodent models of PD have demonstrated neuroprotective and neuroregenerative effects on dopaminergic nigrostiatal function, 28,29 and most recently, intraputamenal infusion in the globus pallidus of MPTP-lesioned rhesus monkeys showed behavioral improvement and elevated locomotor activity levels. 30 Nevertheless, in this study, it was shown that FUS in conjunction with microbubbles can induce high levels of NTN bioavailability through the safely opened BBB volume, and increased bioactivity, indicating the strong therapeutic potential for Parkinson's and other neurodegenerative diseases of this noninvasive drug delivery methodology.…”
Section: Discussionmentioning
confidence: 68%
“…17 Previous studies have shown that GDNF has a strong therapeutic potential in rodents, 18 non-human primates, [19][20][21][22] and PD patients in a phase I clinical trial [23][24][25] with restoration of dopaminergic neurons and functional improvements; however, there have been conflicting findings in phase II clinical trials 26,27 and the studies were halted because of safety concerns, including but not limited to the presence of neutralizing antibodies to GDNF in some patients. As an alternative to GDNF, NTN has been demonstrated to have enormous neuroprotective and neuroregenerative effects on dopaminergic neurons and trophic effects on the parkinsonian brain through intrastriatal injections in rodent PD models, 28,29 convectionenhanced delivery in a non-human primate PD model, 30 as well as intracranial lentiviral (AAV2) injection. 31 AAV2-neurturin gene therapy in PD patients showed that both SN and CP have to be targeted as terminal fields to ensure maximal benefits, 32 and therefore, in the more recent clinical trial, 33 two infusions through one needle tract for the SN and three infusions through three needle tracts in the CP, passing through a single burr hole per hemisphere, were performed.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that intranigral injection of recombinant neurturin induced increases in striatal dopamine release, which were similar in magnitude to those induced by intranigral injection of recombinant GDNF [85]. Intracerebral delivery of recombinant neurturin has also been found to protect nigrostriatal dopaminergic neurones and induce improvements in motor function in MPTP-treated monkeys [86,87]. Co-administration with recombinant neurturin protein has been reported to improve the survival of fetal rat dopaminergic neurones after intrastriatal grafting into 6-OHDA-lesioned adult rats [88].…”
Section: Effects Of Neurturin In Vivomentioning
confidence: 80%
“…A recent study reported that intranigral injection of recombinant neurturin induced increases in striatal dopamine release, which were similar in magnitude to those induced by intranigral injection of recombinant GDNF (Cass & Peters, 2010). Intracerebral delivery of recombinant neurturin has also been found to protect nigrostriatal dopaminergic neurones and induce improvements in motor function in MPTP-treated monkeys (Grondin et al, 2008;Li et al, 2003). Co-administration with recombinant neurturin protein has been reported to improve the survival of fetal rat dopaminergic neurones after intrastriatal grafting into 6-OHDA-lesioned adult rats .…”
Section: Effects Of Neurturin In Vivomentioning
confidence: 80%